2010
DOI: 10.1128/iai.01043-09
|View full text |Cite
|
Sign up to set email alerts
|

Transitions in Oral and Intestinal Microflora Composition and Innate Immune Receptor-Dependent Stimulation during Mouse Development

Abstract: Commensal bacteria possess immunostimulatory activities that can modulate host responses to affect development and homeostasis in the intestine. However, how different populations of resident bacteria stimulate the immune system remains largely unknown. We characterized here the ability of intestinal and oral microflora to stimulate individual pattern recognition receptors (PRRs) in bone marrow-derived macrophages and mesothelial cells. The intestinal but not oral microflora elicited age-and cell type-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 55 publications
(100 reference statements)
7
53
0
Order By: Relevance
“…In detail, sequencing and BLASTN analysis of the 16S rDNA gene in the intestinal contents of the BALB non-CF, Tlr4 ϩ/ϩ mice revealed the majority of the bacteria to be gram positive, in agreement with findings of Hasegawa et al (16) who used a similar technique to define the bacterial species present in the small intestines of C57BL/6 (Tlr4 ϩ/ϩ ) mice. In their study, however, the predominant gram-positive bacteria detected was Erysipelotrichales, and these were not detected in the current work.…”
Section: Discussionsupporting
confidence: 80%
“…In detail, sequencing and BLASTN analysis of the 16S rDNA gene in the intestinal contents of the BALB non-CF, Tlr4 ϩ/ϩ mice revealed the majority of the bacteria to be gram positive, in agreement with findings of Hasegawa et al (16) who used a similar technique to define the bacterial species present in the small intestines of C57BL/6 (Tlr4 ϩ/ϩ ) mice. In their study, however, the predominant gram-positive bacteria detected was Erysipelotrichales, and these were not detected in the current work.…”
Section: Discussionsupporting
confidence: 80%
“…2). Because the composition of the gut microbiota may affect susceptibility to C. difficile infection, we examined the microbiota of Nod1 2/2 and control mice before and after C. difficile infection by denaturing gradient gel electrophoresis (DGGE) (15). We found that the composition of the intestinal microbiota was comparable in Nod1 2/2 and heterozygous Nod1…”
Section: Nod1mentioning
confidence: 99%
“…Moreover, most mouse models of C. albicans GI colonization rely on oral antibiotic treatment (8)(9)(10). Other models rely on the use of germfree mice (11), infant mice (12,13), which harbor a significantly different GI microbiome than adults (14), or specific dietary modifications associated with altered GI microbiota composition (15). Overall, these observations suggest that the microbiota plays a primary role in limiting the colonization of C. albicans in the mammalian GI tract and indicate that dietary interventions could alter this relationship.…”
mentioning
confidence: 99%